2012
DOI: 10.5089/9781475510898.001
|View full text |Cite
|
Sign up to set email alerts
|

Caribbean Growth in an International Perspective: The Role of Tourism and Size

Abstract: After earlier success, growth performance in most Caribbean countries has been disappointing since the early 1990s. With slower growth, output has fallen behind that of relevant comparator countries. This paper analyzes the growth experience of the Caribbean countries from a cross country perspective. Three findings stand out. First, the slowdown in growth is explained more by a decline in productivity rather than a lack of investment. Second, tourism has been a significant contributor to higher growth (throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
1
16
0
1
Order By: Relevance
“…Thacker et al (2012) found that the positive contribution from specializing in tourism has helped to more than offset the negative impact of being a small island economy, and according to the authors tourism has been a significant contributor to lower output volatility in many countries. The latter presents an argument for learning more on the development of tourism demand during a period, let's say a year.…”
Section: Introductionmentioning
confidence: 99%
“…Thacker et al (2012) found that the positive contribution from specializing in tourism has helped to more than offset the negative impact of being a small island economy, and according to the authors tourism has been a significant contributor to lower output volatility in many countries. The latter presents an argument for learning more on the development of tourism demand during a period, let's say a year.…”
Section: Introductionmentioning
confidence: 99%
“…Thacker & Perrelli, (2012) noted, that some studies have tried to investigate the growth performance of Caribbean countries, but not much data was found, thus making building upon previous research difficult. The similarity of these problems within the member countries of OECS shows how the region is affected in the area of higher education development.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Building on the work by Thacker, Acevedo, and Perrelli (2012) on the contribution of tourism to growth in the Caribbean, recent IMF research has focused on assessing the demand factors influencing tourist arrivals, as well as possible supply factors. Specifically, LaFramboise and others (2014) They study the effects on tourist arrivals of demand variables like prices-based on the real effective exchange rate calculated using tourism source market weightsincome and employment in the main source market countries; supply variables, such as the number of hotel beds in the region and the number of airlines flying to the Caribbean; and exogenous factors, such as natural disasters and crime.…”
Section: Tourism In the Caribbean-demand And Supply Factorsmentioning
confidence: 99%
“…Although the literature analyzing this relationship is limited, some studies clearly suggest that tourism does indeed have a positive and significant impact on growth, particularly for low-and middle-income countries (Eugenio-Martín, Martín, and Scarpa 2004). A study by Thacker, Acevedo, and Perrelli (2012) that includes a large group of tourism-dependent small island states finds that tourism not only boosts economic growth, it also helps reduce growth volatility. Specifically, a 10 percent increase in tourist arrivals (as a share of a country's population) raises real per capita GDP growth by about 0.2 percentage point.…”
Section: Introductionmentioning
confidence: 99%